2013
DOI: 10.1073/pnas.1220074110
|View full text |Cite
|
Sign up to set email alerts
|

Rapid electron exchange between surface-exposed bacterial cytochromes and Fe(III) minerals

Abstract: The mineral-respiring bacterium Shewanella oneidensis uses a protein complex, MtrCAB, composed of two decaheme cytochromes, MtrC and MtrA, brought together inside a transmembrane porin, MtrB, to transport electrons across the outer membrane to a variety of mineral-based electron acceptors. A proteoliposome system containing a pool of internalized electron carriers was used to investigate how the topology of the MtrCAB complex relates to its ability to transport electrons across a lipid bilayer to externally lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
209
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(226 citation statements)
references
References 30 publications
(42 reference statements)
14
209
2
Order By: Relevance
“…Therefore, a significant KIE on EET by the OM Cyt  c complex may indicate that the rate of proton removal from the periplasm limits the rate of EET. This idea is in accordance with previous experiments that compared the rate of EET in whole‐cell systems with that of purified OM Cyt  c complexes 12. The in vivo EET rate per OM Cyt  c complex is at least 10‐fold lower (10 2 –10 3  electrons s −1 ) than that in a purified system 13.…”
supporting
confidence: 91%
“…Therefore, a significant KIE on EET by the OM Cyt  c complex may indicate that the rate of proton removal from the periplasm limits the rate of EET. This idea is in accordance with previous experiments that compared the rate of EET in whole‐cell systems with that of purified OM Cyt  c complexes 12. The in vivo EET rate per OM Cyt  c complex is at least 10‐fold lower (10 2 –10 3  electrons s −1 ) than that in a purified system 13.…”
supporting
confidence: 91%
“…In fact, the rates for the thermodynamically unfavorable ET steps do not fall below those for the thermodynamically reversible steps. As a result, the maximum intrinsic electron flux through the heme wire is maintained at 10 4 −10 5 s −1 , just slightly higher than recently measured acceptor-limited transport rates through the multiheme protein complex MtrCAB (18). The structural similarity of MtrF with homologs UndA (19) and MtrC (20) allows us to generalize our findings to these cytochromes also, suggesting an important electron transfer strategy in nature well conserved because of its efficiency for long-range electron transport.…”
Section: Significancesupporting
confidence: 52%
“…4 can be used to interpret recent experiments where MtrCAB was assembled into a proteoliposome and the rates for ET from an internal chemical electron donor (methyl viologen) across the lipid membrane via MtrCAB to solid phase Fe(III) oxides were measured (18). The overall rate constant reported was dependent on the type of Fe(III) mineral used, ranging from 1,133 to 8,500 s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The result is electron transfer from OMMC to the bound flavin cofactor that is 10 3 -to 10 5 -fold faster than to free flavin. Recent studies on MtrCAB-containing proteoliposomes showed that the MtrCAB porin-cytochrome complex represents the minimal requirement for rapid electron transfer to the microbe-mineral interface (17). However, this work does not exclude a role for flavins in enhancing the rates of electron transfer under certain conditions.…”
mentioning
confidence: 64%
“…Protein film voltammetry measurements have shown that S. oneidensis OmcA and MtrC can transfer electrons rapidly and directly to graphite and hematite electrodes (13)(14)(15)(16). Most recently, the MtrCAB complex was reconstituted in proteoliposomes and shown to move electrons rapidly from an intravesicular electron pool to extravesicular nanoparticle suspensions of goethite, hematite, and lepidocrocite (17).…”
mentioning
confidence: 99%